THE SIGNIFICANCE OF USER PARTICIPATION IN ARCHITECTURAL DESIGN: THE CASE OF NICOSIA SOCIAL HOUSING COMPLEX - Sani, Rafooneh Mokhtarshahi; Ulucay, Bahar; Ulucay, Pinar (Archnet-Ijar, 2011)
In both primitive and traditional societies, the user was directly involved in design and construction process of his dwelling, progressively being part of the whole process. However, together with the need to develop for masses of people; and the materialization of architecture as a professional act, the close tie between the individual and his own environment has weakened, creating a ground for little or no user participation, mainly leading to the emergence of passive users. However, in architecture it is extremely important that the end product satisfy the needs of users so that a sense of belonging can be created at long run. Otherwise, the consequences will lead to various problems at cultural, psychological and physical levels leading to a series of changes in the built environment and/or abandonment of building on a permanent basis. The article focuses on a selected case study multi-story social housing schemes-delivered by the government of Northern Cyprus, in the capital city, Nicosia where transformation of user profile led to a series of changes in the built environment, causing the area lose its attraction over the years. Through environment-behavior research tools - focused interviews and observations of physical traces, the study analyses the utilization of open-spaces within the context of existing community texture to reach various arguments for the elucidation of the research problem. The article concludes with recommendations regarding the effect of user participation on place making at large scale social housing schemes.
Keywords: User Participation; social housing; environment-behavior research; place-making